Social Studies and Social Media: Status Among K-12 Tennessee Teachers Before COVID - Kenna, Joshua; Hensley, Matthew (Research in Social Sciences and Technology- OpenED Network, 2023)
Technology integration has received a significant amount of money from the budgets of schools in the United States, even prior to COVID-19. Social media as an instructional tool was also receiving growing attention. However, since COVID-19 it seems that there is an even larger shift in the calls to use social media. The purpose of this study was to report K-12 Tennessee social studies teachers’ self-reported social media use just prior to the COVID-19. Moreover, we compared teachers’ use of social media based on geography, grade level and teaching experience. Statistically significant findings were discovered.